PENENTUAN STATUS MUTU AIR SUNGAI LAE SORAYA KOTA SUBULUSSALAM DENGAN METODE INDEKS PENCEMARAN - Abdul Wahid, Mulyadi; Rohendi, Aulia; Fajri, Rahmat (Department of Environmental Engineering (Prodi Teknik Lingkungan), Fakultas Sains dan Teknologi, UIN Ar-Raniry Banda Aceh, 2023)
The Lae Soraya River, which crosses two provinces, namely North Sumatra and Aceh, is utilized as a raw water source by some communities in the Rundeng District, Subulussalam City, for hygiene and sanitation needs directly without treatment and is also used as a raw water source for drinking. Considering this fact, the researcher studied the water pollution index of this river based on the Minister of Health Regulation number 32 of 2017 and Government Regulation number 22 of 2021, class I. The parameters in this study include temperature, odor, color, pH, Total Dissolved Solids (TDS), Turbidity, and Nitrate. This research aims to provide information on the quality status of the Lae Soraya River so that it can be used for pollution management and control. The method used in this study involves the measurement of the parameters at 7 sampling points through the grab sampling method and the water quality status of the Lae Soraya River is analyzed using the pollution index method (Minister of Environment Decree number 115 of 2003). The results obtained based on the tested parameters are the temperature ranges from 28ºC to 29ºC, the water has a slightly musty odor and a greenish color, pH ranges from 7.8 to 8.4, TDS ranges from 70mg/l to 74mg/l, turbidity ranges from 18.72NTU to 29.17NTU, and Nitrate testing values range from 7.85mg/l to 16.1mg/l. Based on the results, it is found that the Lae Soraya River has a mild pollution status. Considering the testing values and determination of water quality status, the river is not suitable for direct use for hygiene and sanitation needs or as a raw water source for drinking.